Antifouling polysulfone membranes blended with green SiO2 from rice husk ash (RHA) for humic acid separation - Jamalludin, M. R. (2016)
This study investigated the effects of silica prepared from rice husk (RHA) as an antifouling additive in the polysulfone (PSf) membrane. The ultrafiltration mixed matrix PSf/rice husk silica (RHS) flat-sheet membrane was prepared via phase inversion technique at different percentages of silica concentration. The characterization and performance test were conducted on the prepared membrane. The thermal stability of the membrane was observed by using thermogravimetric analysis (TGA). The cross section area and particles distribution of additive were carried out by using the scanning electron microscope (SEM) while the surface morphology was investigated via field emission scanning electron microscope (FESEM). The surface roughness and hydrophilicity were also determined by using atomic force microscopy (AFM) and contact angle measurement respectively. The performance of the membrane was evaluated in terms of pure water flux (PWF), humic acid rejection and antifouling properties. The results of SEM, FESEM and AFM revealed that the incorporating of RHS improved the microstructure of the membrane especially at top layer and sub layer. The results also demonstrated that the mean pore size decreased and the hyrophilicity increased with an increase of RHS particles in PSf membrane. The performance result was found that the addition of RHS in the PSf membrane significantly improved the PWF, rejection and antifouling properties. The results indicated that the addition of 4 g RHS give the highest flux at 300.50 L/m2 h (LMH) and excellent mitigating fouling. The highest rejection was found at 3 g of RHS with a value of 98% for ultraviolet light (UV254) and 96% for Dissolved Organic Carbon (DOC).